Barriers and Challenges Teachers Face with Integrating ICT in Mathematics Teaching - Bhagat, Kaushal Kumar (JOURNAL OF INDIAN EDUCATION, 2012)
The purpose of this study is to explore the barriers preventing the integration and adoption of Information and Communication Technology (ICT) in teaching mathematics. The data were collected by means of questionnaires from secondary school mathematics teachers of Bhubaneswar. Major barriers were identified: lack of time in the school schedule for projects involving ICT, insufficient teacher training opportunities for ICT projects, inadequate technical support for these projects, lack of knowledge about ways to integrate ICT to enhance the curriculum, difficulty in integrating and using different ICT tools in a single lesson, and unavailability of resources at home for the students to access the necessary educational materials. To overcome some of these barriers, this paper proposes an e-portal which is a collection of mathematical tools, a question bank and other resources in digital form that can be used for teaching and learning mathematics. Based on these findings, I propose the use of several strategies that should enhance successful ICT integration.